2010
DOI: 10.1111/j.1365-2893.2009.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic hepatitis C in polytransfused thalassaemic patients: a meta-analysis

Abstract: Hepatitis C virus (HCV) infection is a major cause of liver-related morbidity and mortality among thalassaemic patients. In order to analyse the effect of the current anti-HCV treatment in this subset of HCV-infected patients, we conducted a systematic review with meta-analysis of the available literature. The outcome was sustained viral response. Both comparative [odds ratio (OR)] and non-comparative indeces (success rate) were used to run the meta-analytical procedure. Data encompassing 429 thalassaemic HCV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
7
17
0
2
Order By: Relevance
“…The data on other analyzed SNPs showed that at least three different SNPs had a similar performance in association with SVR in genotype 1 patients. As reported in a previous analysis, 16 and in a meta-analysis by Alavian et al, 27 the rate of SVR in genotype 2 or 3 patients was higher than 60%, and there was no significant association between the SNPs analyzed and SVR in this group of patients. Despite the fact that the lack of correlation with IL28B SNPs may be related to very small numbers of genotype 2 or 3 patients in our cohort, this observation confirms data from other studies 25,[28][29][30] indicating that the prognostic value of SNPs for SVR may be limited to patients with difficult-to-treat genotypes even in this subset of patients.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The data on other analyzed SNPs showed that at least three different SNPs had a similar performance in association with SVR in genotype 1 patients. As reported in a previous analysis, 16 and in a meta-analysis by Alavian et al, 27 the rate of SVR in genotype 2 or 3 patients was higher than 60%, and there was no significant association between the SNPs analyzed and SVR in this group of patients. Despite the fact that the lack of correlation with IL28B SNPs may be related to very small numbers of genotype 2 or 3 patients in our cohort, this observation confirms data from other studies 25,[28][29][30] indicating that the prognostic value of SNPs for SVR may be limited to patients with difficult-to-treat genotypes even in this subset of patients.…”
supporting
confidence: 56%
“…A systematic review with metaanalysis on data from 429 TM patients with chronic HCV hepatitis treated with conventional or PEG-IFN monotherapy, or combination therapy with ribavirin, reported a pooled SVR of 44.7%, and concluded that genotype 1 TM patients significantly benefit from the addition of ribavirin to their therapeutic regimen. 27 There are no published data on the role of IL28B polymorphisms in genotype 1 TM patients treated with PEG-IFN and ribavirin but, as reported in large cohort studies of patients with chronic hepatitis and no hemoglobinopathies, [5][6][7] 'favorable' genotypes of rs12979860 or rs8099917 SNPs should be associated with a best response to standard of care also in this subset of patients, and the evaluation of their predictive values may become a component of future treatment decision-making algorithms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bir meta-analizde PegIFN ve IFN monoterapisiyle veya RBV ile kombine edilerek izlenen 429 talasemili olgu değerlendirilmiştir. HCV genotip 1 infeksiyonunda kombinasyon rejimiyle daha iyi yanıt elde edilmiş, %30-40 daha fazla transfüzyon gerekmiş, ancak ilacı kesecek ölçüde ciddi yan etki gözlenmemiştir (204).…”
Section: Hemoglobinopati Ve Kronik Hepatit Cunclassified
“…was limited by poor tolerance, several contraindications, and concerns about RBV-induced haemolysis and the subsequent increase in transfusion needs (12). More recently, IFN-free regimens, based on directacting antivirals (DAAs), have been developed, showing greater efficacy and tolerance in patients with chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%